Penerapan Konsep Ta’dib dalam Pembelajaran Ekonomi Syariah - Rahmad Hakim (Universitas Muhammadiyah Malang, 2017)
Increasing awareness of Muslims associated with the awareness of the economy in accordance with Islamic values is good news to be grateful. This has the logical consequence that the development of Islamic economics both in the theoretical and practical level is increasing rapidly in proportion to the increasing awareness of Muslims, especially in Indonesia. This study aims to analyze in depth and comprehensively related three important points, namely: first, the concept of ta’dib in Islam. Second, the economic values of sharia economy. Third, the relevance of the concept of ta’dib in Islamic economics. The approach used in this study is literature research by conducting a study and in-depth analysis related to literature related to the concept of ta’dib and Islamic economic values. The result shows that the concept of ta’dib can be applied in the study of Islamic economic accordance with the key concept which stated in the al-Qur’an such as: al-fadlu, ‘adl, maslahah, iqtishad, dan falah. Using those values so that the activity has the motivation (intention) is right and good that is reaching mardhatillah. On the other hand, running an economic activity based on true and good Islamic values is a form of a Muslim's presence against the virtue (al-fadlu) given by Allah to him.